Liberalisation and universal access to basic services telecommunications, water and sanitation, financial services, and electricity. (OECD trade policy studies., 2006)
Building on a recent groundbreaking OECD/World Bank seminar, this volume explores whether and how trade liberaliaation can contribute to achieving universal service goals and the types of complementary policies required. It focuses on experiences in four sectors: telecommunications, water and sanitation, financial services, and electricity. A horizontal assessment also helps determine how far the current services negotiations in the WTO, under the General Agreement on Trade in Services, can aid the attainment of universal service goals.--Publisher's description.